Increase in CEC, K-dd, K Uptake, Si-Total, and Rice Yield (Oryza sativa L.) Due to the Application of Organic and Inorganic Fertilizers, Different Doses on Ultisol - Yuniarti A; D. Herdiyantoro E A; Auliya Auliya (CV. Rayyan Dwi Bharata, 2023)
The Addition Of N, P, K, Nano-Silica, And Straw Compost Is Useful For Providing The Macro And Micro Nutrients Needed By Paddy Rice Plants. Lowland Rice That Is Commonly Cultivated By Farmers Is The Ciherang Variety. In Lowland Rice Cultivation Activities, It Is Often Found That Plants Are Deficient In Nutrients, Especially In Planting Media That Have A Fairly High Acidity Content, Namely Soils Of The Ultisol Order. This Study Aims To Determine The Optimal Fertilization Of N, P, K, Nano-Silica, And Straw Compost To Increase Cec, K-Dd, K Absorption, Si-Total, And Lowland Rice Yields On Ultisol Soils. This Research Was Conducted From September To December 2022 At The Soil Chemistry And Plant Nutrition Experimental Field, Faculty Of Agriculture, Padjadjaran University, Jatinangor, Sumedang, West Java, At An Altitude Of 723 Meters Above Sea Level. The Experimental Design Was Carried Out Using A Randomized Block Design (Rbd) Consisting Of Ten Treatments And Three Replications. Treatment Consisted Of Control (Without N, P, K, Si And Straw Compost); Straw Compost (5 Tonnes Per Hectare) + ½ N, P, K, Si; Straw Compost (5 Tons Per Hectare) + 1 N, P, K, Si; Straw Compost (5 Tonnes Per Hectare) + 1½ N, P, K, Si; Straw Compost (10 Tons Per Hectare) + ½ N, P, K, Si; Straw Compost (10 Tons Per Hectare) + 1 N, P, K, Si; Straw Compost (10 Tonnes Per Hectare) + 1½ N, P, K, Si; Straw Compost (15 Tonnes Per Hectare) + ½ N, P, K, Si; Straw Compost (15 Tonnes Per Hectare) + 1 N, P, K, Si; Straw Compost (15 Tonnes Per Hectare) + 1½ N, P, K, Si. The Results Showed That The Combination Of Fertilizer Doses Of 1 N, P, K , Nano-Silica And 10 Tons Per Hectare Of Straw Compost Gave The Highest Rice Yield With A Dry Harvested Grain Weight Of 11.00 G.Plant-1.